Prognostic indicators for naïve canine non-indolent T-cell lymphoma treated with combination lomustine, vincristine, procarbazine and prednisolone chemotherapy - Blaxill, J.; Buzzacott, Peter; Finlay, J. (2021)
Lomustine, vincristine, procarbazine and prednisolone (LOPP) chemotherapy has been suggested to be an effective treatment for dogs with naïve non-indolent T-cell lymphoma (TCL). Studies evaluating prognostic factors for dogs with TCL treated with LOPP chemotherapy are lacking. The aim of this retrospective study was to assess potential prognostic factors for canine naïve non-indolent TCL treated with the LOPP protocol. This was a retrospective cohort study of naïve non-indolent TCL treated with the LOPP chemotherapy protocol at a single specialty veterinary oncology clinic. Sixty-seven dogs met the inclusion criteria. The outcomes assessed included progression free survival (PFS), overall survival time (OST) and duration of complete response (DCR). The overall median PFS was 118 days (range 7–2302 days). The median OST was 202 days (range 8–2302 days). The overall median DCR was 316 days (range 38–2261 days). Number of treatments administered (p <.0001), multicentric disease (p =.044) and the presence of hypercalcaemia (p =.006) were prognostic indicators for PFS. Increasing number of treatments (p <.0001) and age (p =.0088) were prognostic indicators for OST. To our knowledge, this is the first study to describe hypercalcaemia as a positive prognostic indicator of PFS for TCL treated with LOPP chemotherapy. LOPP chemotherapy can be considered as a first-line treatment protocol against naïve hypercalcaemic non-indolent TCL.